COGNITIVE STYLES AND THEIR INFLUENCE ON LEARNING PREFERENCES IN EARLY CHILDHOOD EDUCATION - Ayu Fajarwati; Clara Mendes; Rafaela Lima (Yayasan Adra Karima Hubbi, 2026)
Early childhood education is increasingly shaped by learner-centered paradigms; however, limited empirical evidence explains how cognitive styles influence learning preferences at this developmental stage. Variability in children’s cognitive processing patterns may contribute to differentiated engagement behaviors, yet research in early childhood contexts remains underdeveloped. This study aims to examine the relationship between cognitive styles and learning preferences among children aged 4–6 years in formal early education settings. A mixed-methods explanatory sequential design was employed involving 162 participants from six institutions. Cognitive styles were measured using developmentally adapted assessment scales, while learning preferences were documented through structured classroom observations. Quantitative data were analyzed using correlation and multiple regression techniques, complemented by qualitative thematic analysis. Results revealed significant associations between visual–spatial orientation and visual–kinesthetic engagement (r = 0.61, p < 0.001), as well as between field-dependence and collaborative learning preference (r = 0.52, p < 0.001). Cognitive styles collectively explained 47% of variance in learning preferences. Findings indicate that cognitive processing tendencies meaningfully shape observable learning behaviors in early childhood classrooms. Recognition of cognitive diversity supports differentiated instructional design and developmentally responsive pedagogical strategies.